A Review on Opioid Dependence, Mechanism and Treatments Used: Option of Treatments: Modern versus Alternative Medicine - Ahmad, Nor Zidah; Mat, Khairi Che; Mohamad, Nasir; Husain, Rohayah Binti; Bakar, Nor Hidayah Abu; Zakaria, Nur Husna; Hashim, Siti Norhajah; Mohd Adnan, Liyana Hazwani; Mohamad Shariff, Mohamad Halim (Bangladesh Journal of Medical Science, 2019)
Opioid dependence is one of the severe social problems encountered by civilization nowadays. Prior to the illicit use of opioid, an abundance of research had been done in order to understand the molecular and cellular action of the opioid. In spite of that, the actual cellular mechanism remains controversial. Hence, this review is targeting on the mechanism of opioid dependence in a biochemical pathway and treatments available either via drug medication or the use of natural remedies to treat opioid dependence. Bangladesh Journal of Medical Science Vol.18(2) 2019 p.171-177